Sistem Pendukung Keputusan Menentukan Peringkat Balita dan Lansia Sehat Menggunakan Metode Analytical Hierarchy Process (AHP) dan Weighted Product (WP) (Studi Kasus: Posyandu Permatasari) - Dieni Anindyasarathi; Imam Cholissodin; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
One of the Posyandu, namely Posyandu Permatasari, every month, a health check is carried out for toddlers and the elderly. This health monitoring is seen from several indicators, the recordes on the Kartu Menuju Sehat (KMS). After that, it will be recorded in the reports and the health ranking of toddlers and elderly will be made. In doing the ranking, currently Posyandu cadres are still doing the sorting by manually comparing toddlers and elderly people. So that it takes quite a long time, and sometimes there are writing errors. Therefore, researchers created a system to rank healthy toddlers and elderly people, which is expected to help increase the effectiveness and efficiency of Posyandu cadres in monitoring progress and making reports easier. This research will be made using the Analytical Hierarchy Process (AHP) method to find the weight of the criteria used and the Weighted Product (WP) to rank each alternative using the weight obtained in the AHP calculation. Based on the result of the tests that have been carried out, for toddler data in testing changes in the value of comparison matrix between criteria, for all matrix changes, the accuracy value was 100% with maximum lambda value of 2, CI value 0, and CR value 0. Meanwhile for the elderly data, in the testing changes in the value of comparison matrix between criteria, the highest accuracy value was 90% wih maximum lambda value of 8,361, CI value 0.05157, and CR value 0.03657.